A Case of Secondary Narcolepsy Presenting with Obstructive Sleep Apnea Symptoms - Sebahat Genç; Hatice Kayim Bilgiç; Emine Esra Okuyucu; Nursel Dikmen; Taskin Duman (Türk Uyku Tıbbı Dergisi, 2016)
Obstructive sleep apnea syndrome (OSAS) and narcolepsy are two diseases causing excessive daytime sleepiness (EDS). As they are often confused, these two disorders can also coexist. Therefore there is need to distinguish these disorders in patients with EDS. We would like to present a case on a patient who sent to our sleep laboratory with a preliminary diagnosis of OSAS and suspicion of narcolepsy in detailed history. The case is a 24 year-old male. He was diagnosed with OSAS and narcolepsy while being investigated for OSAS. Neurological examination revealed an additional diagnosis of multiple sclerosis. In this case report, we emphasize that in patients with EDS, particularly if EDS cannot be explained with OSAS, investigation for narcolepsy should also be done. In addition, when narcolepsy is detected; neurological examination is actually necessary considering the possibility of secondary narcolepsy.